KINERJA DIREKTORAT PELAYANAN USAHA PENANGKAPAN IKAN-KKP SEBAGAI SALAH SATU STAKEHOLDER PERIZINAN USAHA PENANGKAPAN IKAN - Shinta Yuniarta; Sugeng Hari Wisudo; Budhi Hascaryo Iskandar (Bogor Agricultural University, 2011)
Licensing process of fisheries business is conducted on Directorate Fishing Business Service - Ministry of Marine Affair and Fisheries (MMAF), which is the main actor of fisheries business license (Yuniarta 2009). Several constraints of licensing process are found in this research. There are lateness of licensing process in some regions, minimum research development of licensing process and duration of each stage and over all of the stage of licensing process, so that required performance measurement of the directorate. The purpose of this research is measuring performance of Directorate Fishing Business Service based on balanced scorecard approach, that assess on four perspectives, there are learn and growth, business internal process, financial and customer. The result of these perspectives on Directorate Fishing Business Service performance is 3.34, therefore the directorate needs a strategy to increase the performance.